Assessment of the impact of individual loan Provided by commercial banks to entrepreneurs: A case study of selected commercial banks in Tabora town - William, Alex (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for the degree of Master of Business Administration Corporate Management (MBA-CM) of Mzumbe University